Intravenous and Oral Paracetamol Have the Same Effect in Reducing Fever in Pediatric Patients - Fitri Asymida; Yazid Dimyati; Bidasari Lubis; Aznan Lelo; Muhammad Ali; Ayodhia Pitaloka Pasaribu; Syahril Pasaribu (Cell and BioPharmaceutical Institute, 2020)
Background: The antipyretic effect of intravenous versus oral paracetamol is not well known. This study was aimed to compare the antipyretic effect of intravenous and oral paracetamol therapy to reduce fever.Materials and Methods: This was an open-label randomized clinical trial study. The subjects were children who presented to Pediatric Ward and Emergency of Haji Adam Malik Hospital, aged from 2 months to 18 years old, with axillary temperature ≥38.0ºC. Subjects were divided into two groups, group 1 received 15 mg/kg paracetamol intravenous and group 2 received the same dose of paracetamol but given through intravenous. The temperature reduction was analyzed by ANOVA, and the change in temperature was recorded at 0, 15, 30, 60, 120, and 180 minutes after drug administration.Results: In the first group, the mean temperature was decreased (p<0.001) from 15 to 180 minutes after the administration of paracetamol. Nausea was documented as the adverse effect for both oral and intravenous administration groups.Conclusion: The administration of 15 mg/kg paracetamol, either though intravenous or oral, have similar effect in reducing fever in children. Paracetamol therapy though intravenous route can be given if it cannot be given orally.Keywords: antipyretic, pediatrics, fever, intravenous, oral, paracetamol